Tinjauan Yuridis Kekuatan Pembuktian dalam Persidangan Kasus Tindak Pidana Kekerasan Seksual Anak (Studi Putusan Nomor 607/Pid.Sus/2024/PN Srg) - TIARA PUTRI DWI JUNIAR (CV Rewang Rencang, 2025)
Sexual violence against children is a very serious crime that affects the physical, mental and future of the victim. Unfortunately, in the process of proving in court, there are often obstacles caused by the lack of witnesses, physical evidence, and the psychological condition of the victim. This research uses a normative juridical method with reference to a case study focused on Decision Number 607/Pid. Sus/2024/PN Srg. The research findings show that despite the presence of a post mortem and initial testimony from the victim, changes in testimony during the trial became the judge's reason for acquitting the defendant. This highlights weaknesses in the existing evidentiary system. Recommendations from this research are to encourage the application of evidence that is more sensitive to the conditions of victims and strengthen the role of law enforcement to achieve justice.